Evaluation of Pharmacy Manager's Knowledge and Attitude on Extemporaneous Preparation - OKUYAN, BETÜL; ALARÇİN, EMİNE; YAŞAYAN, GÖKÇEN; ŞAHBAZ, SEVİNÇ (MARMARA UNIV, FAC PHARMACY, 2015)
In this work, it is aimed to determine pharmacists' attitude, level of knowledge on extemporaneous formulations including how accurate the formulations are prepared, the problems pharmacists face during preparation, and their approach to solve problems on extemporaneous preparation. Additionally with this work, we aim to gather data on frequently written extemporaneous prescriptions during the recent years. In this work, a questionnaire with the title of Evaluation of pharmacy manager's knowledge and attitude on extemporaneous preparation was applied to pharmacy managers. This questionnaire was completed by 54 community pharmacists. According to our results, it was found that extemporaneous preparations were prescribed to all of the pharmacies that the questionnaire applied, however pharmacists were confronted with various problems during preparation of the formulations.
Keywords: Extemporaneous compounding; community pharmacy; questionnaire